Client involvement in expert advice: Antibiotics in finance? - Andreas Hackethal; Christine Laudenbach; Steffen Meyer; Annika Weber (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
We use minutes from 17,000 financial advisory sessions and corresponding client portfolio data to study how client involvement affects advisor recommendations and portfolio outcomes. We find that advisors confronted with acquiescent clients stick to standards and recommend expensive but well diversified mutual fund portfolios. However, if advisors meet with clients who voice own ideas they deviate markedly from their standards, resulting in poorer portfolio diversification and lower Sharpe ratios. Our findings that advisors cater to client requests parallel the phenomenon of doctors prescribing antibiotics to insistent patients even if inappropriate, and imply that pandering diminishes the quality of advice.
urn:nbn:de:hebis:30:3-472031
Keywords: D14; G11; G21; 330; financial advice; individual investors; client involvement